Analisis Strategi Penjualan Paket Data Internet Pada Konter Andika Cell - Alinda Restu Fauji; Ageng Saepudin Kanda S (Jurnal Riset dan Inovasi Manajemen, 2024)
Andika Cell`s retail counter marketing strategy in attracting customers. Based on interviews conducted at the Andika Cell counter in December 2023, social media marketing and advertising programs were identified as the most important strategies. Social media marketing uses platforms such as Facebook and Instagram to reach a wide audience, while the discount program includes special offers such as free data exchange with the purchase of at least 3 data packages and additional gifts such as the purchase of free tamperglass accessories. Based on analysis, this strategy was successful in increasing sales and improving customer loyalty. To strengthen Andika Cell's position in the market, recommendations were made to optimize social media presence, maintain and improve advertising programs, and develop cross-selling and up-selling strategies.